Obtenção e avaliação de duas populações tropicais de milho indutoras de haploidia - Milani, Klayton Flávio (2013)
The corn, in general, is a very popular food in Brazil and all world. The production of hybrid maize lines can be summarized in three distinct stages: a) obtaition of inbred lines b) evaluation of combining ability of the selected inbred lines, identifying the best combinations c) production and marketing of hybrids. The first step is a slow and costly stage, requiring several successive cycles of selfing. An alternative approach to accelerate this step is the production of inbred lines, by applying the technology of Double-Haploid (DH) by means of haploidy inducer genotype. However, the vast majority of genotypes are inducers of temperate and are not adapted to tropical climate. Therefore, this study aimed to transfer the haploid inducer character from Krasnodar Haploid Inducer (KHI) to two tropical genotypes, a inbred line of field corn (L-47) and a inbred line of popcorn (P9), forming two populations haploid inducers adapted to the tropical climate. In parallel to the study, was also analyzed the efficiency of the separation of putative haploid seeds only by staining anthocyanin endosperm, and the feasibility of the method of cytogenetic chromosome counts for confirmation of true haploid individuals. The new inducer populations were obtained by the standard breeding method by means of crosses and self pollination, and the same were tested for inducibility. The putative haploid seeds were separated and subjected to chromosome counts for confirming the haploid condition. The new inducing populations showed to be efficient in inducing haploidy, forming haploids from maternal origin. The separation of haploid seed endosperm only by staining proved to be inefficient. The technique of chromosome counts was found to be an efficient method, but time consuming and laborious for confirmation of haploid individuals